2017
DOI: 10.3892/mmr.2017.7930
|View full text |Cite
|
Sign up to set email alerts
|

PirB inhibits axonal outgrowth via the PI3K/Akt/mTOR signaling pathway

Abstract: Accumulating data strongly suggests that leukocyte immunoglobulin like receptor B1 (PirB) inhibits axonal outgrowth. However, the underlying mechanisms remain unclear. In the present study, cortical neurons of newborn mice were cultured with Nogo‑66 (Nogo‑p4; 4 µmol/l; a PirB ligand) together with NEP1‑40 (Nogo inhibitory peptide) and/or anti‑PirB body (50 mg/ml). PirB mRNA and protein was higher in cultured neurons induced by Nogo‑66 compared with untreated cells. Neurite outgrowth assays demonstrated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Another study confirmed that elevated microRNA 29a precursor (miR-29a) could promote axonal outgrowth and neurological recovery after ICH by activating the PI3K/AKT/mTOR pathway [ 50 ]. Additionally, leukocyte immunoglobulin-like receptor B1 (PirB) inhibits axonal outgrowth and is involved in the inhibition of the PI3K/AKT/mTOR pathway [ 51 ]. This evidence suggests that the PI3K/AKT/mTOR pathway plays a crucial role in regulating axonal regeneration in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Another study confirmed that elevated microRNA 29a precursor (miR-29a) could promote axonal outgrowth and neurological recovery after ICH by activating the PI3K/AKT/mTOR pathway [ 50 ]. Additionally, leukocyte immunoglobulin-like receptor B1 (PirB) inhibits axonal outgrowth and is involved in the inhibition of the PI3K/AKT/mTOR pathway [ 51 ]. This evidence suggests that the PI3K/AKT/mTOR pathway plays a crucial role in regulating axonal regeneration in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…As NCAM was reported to initiate Src and Akt/mTOR signaling pathways which have regulatory effects on cofilin activation in multiple cells, [25][26][27][28] it is probable that NCAM regulates the activation of cofilin in human F I G U R E 3 NCAM knockdown suppressed the EMT-like phenotype in A375 and M102 cells. (A) The cell morphology transformation of A375 and M102 cells transfected with NCAM downregulation vectors.…”
Section: The Src/akt/mtor Pathway Participates In Ncam-mediated Cofmentioning
confidence: 99%
“…Through alternate downstream pathways, the neuronal receptor paired Ig-like receptor B, which has common ligands with Nogo-66 receptor-1 (NgR1), can prevent the lengthening of axons. [ 17 18 19 ] Axonal growth is also blocked by a combination of the Rho/ROCK pathway and interactions between the sphingosine-1-phosphate receptor 2 in neurons and a specific Nogo-A region. [ 20 ] By helping NgR1 mature and utilizing the Rho/ROCK pathway, the nociception receptor ORL1 also hampers axon extension.…”
Section: Neurons and Oligodendrocytesmentioning
confidence: 99%